ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL TERHADAP KEPUTUSAN PERSETUJUAN PEMBIAYAAN MUSYARAKAH DI PT. BPR SYARIAH JABAL TSUR PANDAAN - Fahmul Iltiham, Muhammad (MALIA (TERAKREDITASI), 2017)
In the midst of modern society today the problem of investment has been the development of financial activity (financial asset) so rapidly. Lately sharia investment is increasingly crowded because of the public interest in sharia-based investment.There is a positive relationship between the level of investment and the expected rate of return. Investment demand (investment demand) is determined by the level of profit (expected profit).While the expected profit level depends on (1) the total expected profit from firm activity (entrepreneurial) (2) Share in profit claimed by the owner of the fund. Thus, Muslim investors or savers may choose between three alternatives to take advantage of their funds (a) hold cash in cash (b) hold funds in the form of non-revenue assets (eg bank deposits, loans, property, jewelery) or (C) investing funds (becoming an investor in a project that can increase the state capital stock).